Vendor Selection for The Procurement of Gold Crusher at PT. ILBB Using Analytic Hierarchy Process - Jeremiah Martua, Reginald; Sunitiyoso, Yos (CV. Green Publisher Indonesia, 2025)
This research aims to address the issue of vendor selection for the procurement of a gold crusher, a primary need for PT. Indotan Lombok Barat Bangkit (ILBB) in its transition from exploration to gold production. Choosing the right vendor is crucial as it directly impacts the sustainability of the company's business operations. The study employs the Analytical Hierarchy Process (AHP) to evaluate three vendor alternatives: Liming, Jinpeng, and Yifan, based on five main criteria: Financial, Delivery, After-sales, Machine, and Vendor Credibility, which were developed through a combination of literature reviews and interviews with ILBB decision-makers. The analysis results indicate that the Machine criterion is the top priority with a weight of 49.1%, particularly focusing on the sub-criterion of Machine Reliability. This reflects ILBB's emphasis on operational efficiency and production stability. Vendor Credibility ranks second with a weight of 23.65%, highlighting the importance of trust in the vendor's ability to meet the company's needs. The After Sales criterion ranks third, with the availability of spare parts sub-criterion being a major consideration to ensure operational continuity. The timeliness of the delivery sub-criterion within the Delivery criterion also plays a significant role, whereas the financial criterion is less prioritized. Liming emerges as the best choice with a priority weight of 52.15%, excelling in sub-criteria such as Machine Reliability, Machine Technology, and Manufacturing Standards, aligning with ILBB’s strategic and operational needs. This study demonstrates that AHP effectively supports multi-criteria decision-making processes, offering a replicable methodology applicable to other companies with similar challenges.